Fugitive colours - Hossain, Selina, 1947-; Zaman, Niaz. (Dhaka : Writers.ink : Distributed by University Press, 2010)
Selection of English translated short stories.
ENH
Keywords: Hossain, Selina, -- 1947- -- Translations into English; Short stories, Bengali -- Translations into English